2014
DOI: 10.1093/schbul/sbu121
|View full text |Cite
|
Sign up to set email alerts
|

Increased Resting-State Gamma-Band Connectivity in First-Episode Schizophrenia

Abstract: Background: Schizophrenia has long been suggested to represent a disorder with prominent neural dysconnectivity. Gamma-band oscillations are highly relevant in this context, due both to their proposed involvement in neuronal synchronization and to their association with neurotransmitter systems relevant for schizophrenia. Several task-related studies have confirmed reduced power and synchronization of gamma-band oscillations in schizophrenia, but it has been suggested that these findings might not apply to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
92
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(102 citation statements)
references
References 93 publications
(111 reference statements)
8
92
1
1
Order By: Relevance
“…This finding is of particular relevance to understanding brain mechanisms involved in working memory deficits because gamma amplitude scales with the number of items maintained in working memory (Roux et al, 2012) and task related reduction in gamma amplitude is associated with compromised working memory performance (Yamamoto et al, 2014). Recent report relate illness severity to exaggerated fronto-parietal gamma band connectivity during resting conditions (Andreou et al, 2014) strengthening the notion of global network deficiency yet mediated by local events in the gamma band. Brain's intrinsic organization during rest commonly known as the default mode network (DMN) is likely determining network organization during cognitive demands (Raichle, 2015a, b).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This finding is of particular relevance to understanding brain mechanisms involved in working memory deficits because gamma amplitude scales with the number of items maintained in working memory (Roux et al, 2012) and task related reduction in gamma amplitude is associated with compromised working memory performance (Yamamoto et al, 2014). Recent report relate illness severity to exaggerated fronto-parietal gamma band connectivity during resting conditions (Andreou et al, 2014) strengthening the notion of global network deficiency yet mediated by local events in the gamma band. Brain's intrinsic organization during rest commonly known as the default mode network (DMN) is likely determining network organization during cognitive demands (Raichle, 2015a, b).…”
Section: Discussionmentioning
confidence: 87%
“…and Knight, 2010), exaggeration of clocked gamma power might have a detrimental influence on task-related processing and behavior when already elevated at rest (Andreou et al, 2014;Gandal et al, 2012). PAC was found in both samples, its increase in SZ undermines the utility of cross-frequency coupling in HC (Axmacher et al, 2010;Canolty and Knight, 2010).…”
mentioning
confidence: 89%
“…It is to those patients that pharmacological targeting to increase gamma-band activity may be of benefit. These effects may not apply to those patients that exhibit increased gamma-band activity (Andreou et al 2014;Diez et al 2014), further emphasizing the heterogeneous nature of the population. We have preliminary evidence suggesting that the stimulant modafinil may indeed compensate to some extent for excessive amounts of NCS-1.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, connectivity scores during a cognitive task indicate that there is a decrease in activity of the right anterior insula, which is part of the SN, among patients with hallucinations. Other studies have linked alterations in resting state gamma band connectivity and the core symptoms of schizophrenia with EEG (Andreou et al, 2014b;Sun et al, 2014). Studies have found that there is an increase resting gamma activity in schizophrenia using MEG (Kim et al, 2014).…”
Section: Inherent Noise and Relationship To Symptoms In Schizophreniamentioning
confidence: 99%